Las responsabilidades y sanciones por nepotismo según la ley organica del servidor pùblico (losep). - Castro Pallaroso, Juan Carlos (2014)
Nepotism is the act by which an officer or authority of the Public Administration or other organs of the state, which has the ability to appoint or hire a servant or public servant, he does regarding relatives to the fourth degree of consanguinity, degree of affinity or for reasons of marriage; or when the aforementioned officials exert direct or indirect interference in the appointment and recruitment. It is so exposed that nepotism is considered inadequate because practice encourages a conflict of interest between personal interest and public service; other hand, restricts access equal to public service, makes it difficult for public entities can objectively fulfill the functions for which they were created; weakens a healthy environment for the internal control and evaluation; and even disrupt labor discipline due to the lack of impartiality of the superior power to exercise control on an equal footing on servers linked to officials familiar with decision-making. According to the Royal Spanish Academy, nepotism is some give undue preference to relatives for concessions or public employment. Article 6 of the Organic Law of the Public Service, says is the illegal act committed by an official in the designation made within the same institution, for the spouse, partner or relatives including the fourth degree of consanguinity and second of affinity. Article 7 of the above Act, prosecutes our research topic, in what has to do with the responsibilities and penalties for nepotism, the same notes: "Without prejudice to administrative, civil or criminal liability that might arise, have no legal validity, not cause any economic and egress will be void, appointments or contracts incur in the cases specified in Article 6 of this Act Shall be punished with dismissal from their previous position due process the appointing authority to appoint or hire staff against the prohibition of nepotism established in this Act, together with the illegally appointed or hired person also shall be jointly liable for the payment of wages erogadas by the Institution The head of the Unit Management Human Resource as well as the server or server manager that knowing the existence of some causal nepotism, any possible registration appointment or contract shall be jointly and severally liable overpayment pointed out in this article. Excluded from this sanction to servers prior to registration and possession of appointment or contract notified in writing to the appointing authority for not complying with this rule. " The strict legal standard set forth above relates to the constitutional mandate through Article 230 paragraph 2 prohibits the public practice when operating the figure of nepotism, hence the importance of the proper object of this research is the establishment of responsibilities and sanctions when these are met within the public administration and other state bodies.